Experimental results from non-sub-wavelength gold grating-coupled surface plasmon resonance using a monochromatic signal for gold/air interface as the base for biosensors - Ponce Camacho, Miguel Ángel; López-Leyva, Josué Aarón; Casemiro-Oliveira, Leiva (My University, 2020)
In this paper, a gold diffraction grating is used to generate surface Plasmon resonance using a ppolarized monochromatic incident signal (λ = 650 nm) and a dimensional ratio between wavelength and spatial period of metallic grating less than the unit (λ/ d <; 1) for gold/air interface. The surface Plasmon resonance was detected using the angular detection technique. The experimental results show that the resonance angle is ≈15.75° and it is close to the theoretical results calculated (≈15.17°) for the gold diffraction grating. The preliminary results are important for the research and technical development of low-cost biosensors.
Indexación SCOPUS
Keywords: Integrated optics; Gold; Optical polarization; Biomedical optical imagin; Campus Ensenada